2022
DOI: 10.3390/ijms23158733
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Enhances Hippocampal Glucose Metabolism in an In Vitro Mice Model of Alzheimer’s Disease

Abstract: Impaired cerebral glucose metabolism is an early event that contributes to the pathogenesis of Alzheimer’s disease (AD). Importantly, restoring glucose availability by pharmacological agents or genetic manipulation has been shown to protect against Aβ toxicity, ameliorate AD pathology, and increase lifespan. Lithium, a therapeutic agent widely used as a treatment for mood disorders, has been shown to attenuate AD pathology and promote glucose metabolism in skeletal muscle. However, despite its widespread use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 103 publications
1
3
0
Order By: Relevance
“…However, the outcome on this matter was rather inconclusive. Lithium has previously shown to affect glycogen synthesis and glucose availability of peripheral tissues in mammalian models through inhibition of GSK‐3 61,74,90 . According to our results, however, no changes in GSK‐3‐dependent glycogen accumulation were observed in Drosophila oocytes in response to lithium.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…However, the outcome on this matter was rather inconclusive. Lithium has previously shown to affect glycogen synthesis and glucose availability of peripheral tissues in mammalian models through inhibition of GSK‐3 61,74,90 . According to our results, however, no changes in GSK‐3‐dependent glycogen accumulation were observed in Drosophila oocytes in response to lithium.…”
Section: Discussionsupporting
confidence: 45%
“…Lithium has previously shown to affect glycogen synthesis and glucose availability of peripheral tissues in mammalian models through inhibition of GSK-3. 61,74,90 According to our results, however, no changes in GSK-3-dependent glycogen accumulation were observed in Drosophila oocytes in response to lithium. Likewise, we did not detect any significant impact of lithium on inhibitory phosphorylation of GSK-3 in the ovaries of lithium-treated females.…”
Section: Discussionmentioning
confidence: 40%
“…16 In addition, another in vitro Animal study trials have shown that lithium also cause the affection of glucose metabolism on mouse's hippocampal when the mouse carry AD. 17 Furthermore, in a Meta-analysis included 3 randomized controlled studies (n=232), in this analysis, researchers assess the lithium effectiveness AD's patients and people who carry cognitive impairments. The feedback is, compare with the placebo, Lithium involved cognitive recoveries of patients gets a significant enhancement in AD and cognitive dysfunction (MD = -0.41, 95%CI = -0.81 to -0.02, P = 0.04, I2 = 47%).…”
Section: Effectivenessmentioning
confidence: 99%
“…Recently, Ates et al [ 173 ] presented evidence that neuroprotection by lithium depends on GSK3ß phosphorylation along the Akt pathway. Under drug treatment, hippocampal glucose uptake is enhanced by a strong increase in Glut3 [ 174 ]. Although Akt signaling is the main pathway to increase glucose uptake, involvement of AMPK/insulin receptor signaling is very likely—at least in the transgenic AD mouse.…”
Section: Protective Treatmentsmentioning
confidence: 99%